Prospect for vegetative bulbs productions and enlargement of rose onion (Allium cepa L.) via agro-physiological optimization in tropical climate - Krishnamoorthy, Mahaletchumy; Kamaruzali, Afiq; Toh, Liang Su; Mohd Sahud, Nurul Aaliyah; Khairulazlan, Khairunnisa Najwa; Jusoh, Mashitah; Muhamad Mujab, Azzami Adam; Khalid, Khalisanni (Sebelas Maret University, 2025)
Rose onion (Allium cepa L.), a unique red onion from Karnataka, India, is valued across Asia for its culinary significance. Recent onion supply disruptions have triggered an export ban from India, causing price surges and declining onion quality. This study evaluated two agro-physiological cultivation methods for rose onion under tropical Malaysian conditions to address Malaysia’s onion import dependency. The bulbification method aimed at optimizing planting material production utilized open field conditions and resulted in enhanced pseudostem proliferation (p < 0.001) and increased bulb counts (p < 0.001). In contrast, the bulking method, designed to maximize yield, employed shaded environments and nutrient management, achieving an 86% yield increase (10.78 tons ha-1) and higher economic returns (102,410 MYR ha-1). Key physiological measurements, including chlorophyll content (+30.68%, p < 0.05) and water-use efficiency (+87.71%, p = 0.003), highlighted the adaptability of both methods to tropical climates. Economic analysis revealed that although pre-harvest costs were 65% higher for the bulking method, it generated 63,715 MYR in net profit, representing a 450% increase in profitability and a benefit-cost ratio (BCR) of 2.65. The findings support targeted cultivation strategies based on production objectives and emphasize the agronomic value of integrating physiological monitoring and cost-benefit analysis in tropical onion systems.